Perceptions and practices of farmers of indigenous poultry towards Salmonella infections in North-Central Nigeria - Nancy Milton Sati; Pam Dachung Luka; Frank Norbert Mwiine; Idowu Oluwabunmi Fagbamila; Rebecca Paul Weka; Maryam Muhammad; Joseph Erume (Open Veterinary Journal, 2022)
Background: Salmonella infections continue to be of global concern to poultry health, productivity, and public health. About 44% of the poultry in Nigeria are indigenous, and kept in close interaction with farmers who are mostly rural dwellers and have limited access to veterinary and extension services. Aim: The perceptions and practices of farmers of indigenous poultry towards Salmonella infections were assessed in order to obtain and document baseline data that can be used to create awareness among farmers about these infections and their attendant public health implications. Methods: A cross-sectional approach using a multi-stage sampling method was used in this survey. A total of 419 farmers keeping indigenous poultry were interviewed using a pre-tested electronic questionnaire in three randomly selected States within North-Central Nigeria. Data were analyzed using descriptive and regression analysis. Results: Out of the 419 respondents, 138 (32.9%), 141 (33.7%), and 140 (33.4%) were from Benue, Kwara, and Plateau States respectively. Of the 419, 55.4% were females, 40.8% were above 40 years, and 35.8% have over 10 years farming experience. Majority of the poultry are not housed (58.5%) and farmers predominantly rear chickens (51.8%). Also, 49.9% of the birds were 1-6 months with 41.5% of the flock sizes being 11-20. Respondents had a poor level of perception towards Salmonella infection as the majority did not know that Salmonella affects poultry (89.3%) and that Salmonella infections are zoonotic (94.5%). Significant (p =0.000) associations existed between categorized perception score and age, educational status, family size, and farming experience of farmers. There were significant (p = 0.000) associations of categorized practice scores with gender, age, education status, family size, and farming experience of farmers. Conclusion: This study has revealed the poor perception of farmers on Salmonella infections and has highlighted their practices. There is a need to raise awareness about these infections so as to improve indigenous poultry health and productivity as well as public health.